PENERAPAN METODE PRAKTIKUM UNTUK MENINGKATKAN PEMAHAMAN KONSEP MAHASISWA - Gusti Handayani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2019)
The aim of this research is to know the implementation of experiment method to increase students’ understanding on concept in Konsep Dasar IPA II course. The kind of research done was Classroom Action Research. Which consisted of two cycles. The subject of the research was the undergraduate students of PGMI semester III class 1. The number of the students were 37. The result indicated that the students got improve in each cycle. In cycle I, Activity 1 and 2 the students were in the fair level, while in activity 3 until 6 stepped up into good level. Next, in cycle II, activity 1 until 4 the students got good, while four other activities got very good. Meanwhile the students understanding got improve from cycle 1 to cycle 2 with the mean score of the test was 77.0 while cycle II was 77.45. The improvement from pre test to cycle I was 11.55 point, for cycle II the improvement was 12 points. So, the conclusion is the experiment method can improve students’ understanding on concept.